Space : a visual encyclopedia. (DK Publishing, 2020)
Presents a comprehensive encyclopedia of space featuring illustrated entries on the sun, planets, moons, galaxies, black holes, and stars among other objects. Includes hundreds of images from NASA, fact boxes, timelines, and a glossary.